Respuesta :

Answer:

Step-by-step explanation:

6x + 3y = -18

Taking 3 common from left side

so, 3(2x+y) = -18

2x+y = -18/3

2x+y = -6 (equation 1)

and, 7x + 7y = 0

Taking 7 as commom from left side

7(x + y) = 0

x + y = 0/7

x + y = 0 (equation 2)

now , by using elimination method

subtracting equation2 from equation1

2x + y - (x + y)= -6 - 0

2x + y - x - y = -6

x = -6

so, x = -6

substituting value of x in equation 1

2(-6) + y = -6

-12 + y = -6

y = -6 +12

y = 6

hence, the value of x = -6

          and value of  y = 6